Julia Child a life - Shapiro, Laura (New York Lipper/Penguin, 2009)
One of the most beloved figures in 20th century American culture was Julia Child, television's bouyant "French Chef." With an irrepressible sense of humor and a passion for good food, Child ushered in the nation's culinary renaissance and became its chief icon. Millions watched as she spun threads of caramel, wielded live lobsters, flipped omelets and unmolded spectacular desserts. Her occasional disasters, and brilliant recoveries, were legendary. Yet every step of the way she was teaching carefully crafted lessons about ingredients, culinary technique, and why good home cooking still matters. Her open-hearted approach to the kitchen was a lesson in how to live. Food writer Shapiro describes Child's unlikely career path, from California party girl to her marriage to Paul Child, to cool-headed chief clerk in a World War II spy station, to bumbling amateur cook, and finally to the classes at the Cordon Bleu in Paris that changed her life.--From publisher description.
Hungry -- Prof. Julia -- How to make things taste the way they should -- The performance of me -- Real male men -- I am getting very tired of kiwi fruit -- She likes to eat.
First published in the United States of America by Viking Penguin: 2007.
Keywords: Child, Julia; Cooks -- United States -- Biography